Analisis Dampak Model Pelatihan Klasikal dan Preseptorsip terhadap Kompetensi serta Perbedaan Capaian Kompetensinya (Studi Kuasi Eksperimental di RSAB Harapan Kita) - Suprapti, Sri (Jurnal Ilmiah Administrasi Publik, 2019)
The purpose of this research is to find out the effect of classical and preceptorship training models on the competence attainment. The research used quasi experimental method, non-randomized control group pre-test and post-test design. The analysis was conducted usingdiffernt test and simple linear regression test. Results show there was a significant difference in the competence. Average achievement of competencies between the classical traing model and the preceptorship have no significant differences. The average of competence attainment of the preceptorship model was greater. Based on participants’ perceptions, classical training model has a positive but insignificant, while preceptorship training model has positive and significant effect on competency achievement. It was concluded that both classical and preceptorship model affects the enhancement of competence after training. The difference is that preceptorship model results in greater enhancement classical training model.